Шпинелиды мантийных пород - Мацюк С. С. Станислав Степанович; Платонов А. Н. Алексей Николаевич; Польшин Э. В. Эрнст Васильевич; Таран М. Н.; Павлишин В. И. Владимир Иванович (Киев, Наукова думка, 1989)
Авт. указаны на обороте тит. л.